2014
DOI: 10.1002/cctc.201402547
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated Core‐Shell Magnetic Nanoparticle (Fe3O4@SiO2@PrSO3H) as a Highly Active and Durable Protonic Acid Catalyst; Synthesis of Coumarin Derivatives through Pechmann Reaction

Abstract: Sulfonic acid supported silica coated magnetic nanoparticles (Fe3O4@SiO2@PrSO3H), was prepared by using low cost precursors and a facile immobilization technique. The final catalyst, which was characterized by XRD, FT‐IR, vibrating sample magnetometer (VSM), TEM, and TGA techniques, was found to be an efficient and environmentally benign solid acid for the Pechmann condensation of substituted phenols with ethyl acetoacetate leading to the formation of coumarin derivatives. After the reaction, the catalyst coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Compared to previous reports [25,[42][43][44][45][46][52][53][54][55][56][57][58], this study also demonstrated that the surface area of the catalytic systems can be manipulated by the synthetic methodology. As can be observed from the obtained data, the acidic SiO 2 catalyst varies in the surface area in comparison to the one prepared from TEOS and displays more activity towards the Pechmann reaction.…”
Section: Methodsmentioning
confidence: 41%
See 1 more Smart Citation
“…Compared to previous reports [25,[42][43][44][45][46][52][53][54][55][56][57][58], this study also demonstrated that the surface area of the catalytic systems can be manipulated by the synthetic methodology. As can be observed from the obtained data, the acidic SiO 2 catalyst varies in the surface area in comparison to the one prepared from TEOS and displays more activity towards the Pechmann reaction.…”
Section: Methodsmentioning
confidence: 41%
“…Meanwhile, Zareyee and Serehneh [43] employed CMK-5 adapted by sulfonic acid as a catalyst to synthesize coumarin from substituted phenols and ethylacetoacetate. Other reports explored successful attempts of using sulfonated magnetic nanoparticles in forming coumarin derivatives [44,45]. Sulfonated mesoporous silica has also been utilized to prepare 7-hydroxy-4-methyl coumarin [46].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our experience in design and application of novel nanostructured catalysts in recent years, [17,[60][61][62][63][64][65] the nanocatalyst CNC-AMPD-Pd was prepared by route depicted in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30][31][32] Nowadays with the advancement of nanoscience, magnetic nanoparticles (MNPs) as an effective heterogeneous catalyst have been widely synthesized and used efficiently in various organic syntheses. [33][34][35][36][37][38][39][40][41] In addition to common properties of all nanoparticles such as the high surface area, as well as chemical and thermal stability, MNPs could be separated easily from reaction mixture using an external magnet. Immobilization of various shells such as silica and carbon on the surface of MNPs protects them against agglomeration and improves the chemical stability of MNps from environmental degradation and also provide an appropriate surface for further modification while the magnetic core causes easy separation using an external magnet.…”
Section: Introductionmentioning
confidence: 99%